Incorporating Cyano Groups to a Conjugated Polymer Based on Double B←N-Bridged Bipyridine Units for Unipolar n-Type Organic Field-Effect Transistors - Cao, Xu; Min, Yang; Tian, Hongkun; Liu, Jun (Organic Materials, 2021)
The development of n-type semiconductors lags far behind that of their p-type counterparts, demonstrating the exploration of exclusive n-type π-conjugated polymers is significant. The double B←N-bridged bipyridine (BNBP)-based polymers P-BNBP-TVT containing (E)-1,2-di(thiophen-2-yl)ethene (TVT) previously reported exhibits ambipolar character because of the electron-rich nature. Herein, we incorporated strong electron-withdrawing cyano groups into the 3,3′-positions of the TVT moiety to a copolymer P-BNBP-2CNTVT to develop n-type π-conjugated polymers. The LUMO/HOMO energy levels of P-BNBP-2CNTVT are −3.80/−5.95 eV, respectively, which are ~0.4 eV lower than that of P-BNBP-TVT without cyano groups. Unsurprisingly, compared with ambipolar P-BNBP-TVT, the organic field-effect transistors (OFETs) based on P-BNBP-2CNTVT showed unipolar n-type characteristics with an electron mobility of 0.026 cm2 · V−1 · s−1 and a lower threshold voltage of ~25 V as well as high Ion/Ioff of ~105. This study demonstrates that organoboron π-conjugated polymers could be regarded as a tool for constructing exclusive n-type semiconducting polymers used in OFETs.
Keywords: π-conjugated polymers; cyano-functionalization; organic field-effect transistors; electron transports; n-type polymer semiconductors